RU28318, an Aldosterone Antagonist, in Combination with an ACE Inhibitor and Angiotensin Receptor Blocker Attenuates Cardiac Dysfunction in Diabetes - Ibrahim F. Benter; Fawzi Babiker; Ibrahim Al-Rashdan; Mariam Yousif; Saghir Akhtar (Journal of Diabetes Research)
Aims. We evaluated the effects of RU28318 (RU), a selective mineralocorticoid receptor (MR) antagonist, Captopril (Capt), an angiotensin converting enzyme inhibitor, and Losartan (Los), an angiotensin receptor blocker, alone or in combination with ischemia/reperfusion- (I/R-) induced cardiac dysfunction in hearts obtained from normal and diabetic rats. Methods. Isolated hearts were perfused for 30 min and then subjected to 30 min of global ischemia (I) followed by a period of 30 min of reperfusion (R). Drugs were administered for 30 min either before or after ischemia. Drug regimens tested were RU, Capt, Los, RU + Capt, RU + Los, Capt + Los, and RU + Capt + Los (Triple). Recovery of cardiac hemodynamics was evaluated. Results. Recovery of cardiac function was up to 5-fold worse in hearts obtained from diabetic animals compared to controls. Treatment with RU was generally better in preventing or reversing ischemia-induced cardiac dysfunction in normal hearts compared to treatment with Capt or Los alone. In diabetic hearts, RU was generally similarly effective as Capt or Los treatment. Conclusions. RU treatment locally might be considered as an effective therapy or preventative measure in cardiac I/R injury. Importantly, RU was the most effective at improving -dP/dt (a measure of diastolic function) when administered to diabetic hearts after ischemia.